2020
DOI: 10.3390/su12030856
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Traffic Crashes in Italy: An Explorative Analysis among Different Driving Circumstances

Abstract: Analyzing traffic accidents is very important due to their direct impact on the social environment. In the literature, many studies focus on the different aspects that influence traffic accidents, such as human, vehicle, road and environment risk factors. In this paper, we propose a methodology for testing the relationship between road, external environment, driver and vehicle characteristics, and certain circumstances that lead to the traffic crashes. Particularly, we elaborate on logistic regression models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…According to Michon (1979) , dangers, such as the risk of being involved in an accident, will occur with some probabilities while driving. A number of factors, acting alone or connected, could cause accidents to occur, such as vehicle (i.e., tires’ conditions), road (i.e., road grip), environmental (i.e., weather conditions), and human (i.e., cognitive failures, attentional blinks) factors ( Treat et al, 1979 ; Evans, 1991 ; Eboli and Forciniti, 2020 ). Human factors, which are considered the cause of more than 70% of road accidents ( Evans, 1996 ; Petridou and Moustaki, 2000 ; Istat, 2019 ), refer to an individuals’ driving skills, driving style, cognitive abilities, and personality measures ( Evans, 1991 ; Elander et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Michon (1979) , dangers, such as the risk of being involved in an accident, will occur with some probabilities while driving. A number of factors, acting alone or connected, could cause accidents to occur, such as vehicle (i.e., tires’ conditions), road (i.e., road grip), environmental (i.e., weather conditions), and human (i.e., cognitive failures, attentional blinks) factors ( Treat et al, 1979 ; Evans, 1991 ; Eboli and Forciniti, 2020 ). Human factors, which are considered the cause of more than 70% of road accidents ( Evans, 1996 ; Petridou and Moustaki, 2000 ; Istat, 2019 ), refer to an individuals’ driving skills, driving style, cognitive abilities, and personality measures ( Evans, 1991 ; Elander et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing different land use types, the results show that non-categorized zones (NC) have the highest injuring crash probability, followed by industrial and residential, if commercial zones are the reference category (2.8, 2.1, and 1.3 times greater, respectively). Several studies (e.g., [17,[43][44][45][46][47]) present similar findings about the outcomes of crashes in segments with intense activity (commercial, residential, etc. ).…”
Section: Urban Factorsmentioning
confidence: 67%
“…In addition, this study considers the neighborhood scale (NESC) and land use (LUSE). The effect of such factors has been analyzed and discussed in previous studies [18,43], and it is thought that widely dispersed developments and low density often increase vehicle miles traveled, this magnitude being directly related to higher crash rates and severity. Our study also showed that being in a large-scale neighborhood increases the odds ratio of injuring crashes by a factor of 6.7.…”
Section: Urban Factorsmentioning
confidence: 99%
“…Factors influencing the injury severity of traffic accidents have been discussed by many scholars. Previous studies indicated that factors affecting the severity of road traffic accidents include the age of the motor vehicle driver [6], aggressive driving behavior [7], driving experience [8], drunk driving [9], weather [10], road infrastructure [11], hazardous materials transportation [12], accident circumstances [13], etc.…”
Section: Literature Reviewmentioning
confidence: 99%